The role of ethics education in reducing job corruption - Al - Amri, Fawaz bin Ali (Journal of Economic, Administrative and Legal Sciences, 2017)
This research aims to highlight the role of awareness in the ethics of the profession and its impact in reducing job corruption by answering the main question of the research (What is the role of education in the ethics of the profession in reducing the corruption of career?). The descriptive analytical approach was used as it is one of the methods that contribute to the study and analysis of human and social phenomena to achieve the objectives of the research and answer its questions. The researcher adopted the questionnaire as a data collection tool. The survey was conducted in a sample consisting of 220 public and private sector employees in the Kingdom of Saudi Arabia randomly chosen through social networking sites. The researcher found many results، most important of which are that the members of the research sample have the knowledge and ability to distinguish the functional practices and determine whether they are considered functional corruption in both large and small or that they do not represent corruption. its drew the researcher’s attention to the fact that more than half of the research sample did not attend awareness courses about ethics of the profession، and half of them did not have the knowledge of the way to report on the confirmed or probable corruption. Therefore، 84.6% of the sample believes that the employees in their establishments need more awareness about the ethics of the profession and its importance and the methods of reporting cases of confirmed and potential corruption. It is important to note that the majority of respondents believe that the spread of corruption negatively affects the performance of employees and hinders the achievement of the objectives of the employer. The majority also believe that the reduction of corruption in general contribute in achieving the vision of the Kingdom of Saudi Arabia 2030. It was confirmed to the researcher that the majority of the sample expect the reducing of corruption by increasing the awareness of employees and their knowledge of the ethics of the profession.